Power-load aware multipath routing protocols for MANET - Praba, R.; Subasree, S.; K. Sakthivel, N (International Journal of Engineering and Technology, 2019)
The Mobile Ad Hoc Network (MANET) is a group of Wireless Mobile Nodes with restricted Power Supply that dynamically form a temporary network and can communicate each other without the support of any established infrastructure. It was noticed that the routing is one of the major challenges in MANET due to the mobility nature. This research work has identified recently proposed two Routing Techniques namely i. Fitness Function based Ad Hoc On Demand Multipath Distance Vector Routing Protocol (FF-AOMDV) and Secure Three Fish Distributed Routing (STFDR). These two techniques were implemented and studied thoroughly in terms of Throughput, Dropping rate, Packet Delivery Ratio, Packet Loss Ratio, Energy Consumption and End-to-End delay. The experimental results clearly demonstrate that the FF-AOMDV outperformed when compare with STFDR under major network per-formance parameters. This Research Work noticed that the FF-AOMDV unable to address Power Dissipation that leads link failure. This minimizes the life time of the MANET. This work proposed an efficient Power-Load Aware Multipath Routing Protocol (PLA-AOMDV) to address the above-mentioned issue. The PLA-AOMDV is designed and implemented in QualNet 6.1 and results were studied thoroughly in terms of Throughput, Packet Dropping Rate, Routing Overhead, Energy Consumption, End-to-End De-lay, Life Time (Dead Nodes Count). From the experimental results, it was established that the proposed Power-Load Aware Multi-Path Routing Protocol (PLA-AOMDV) is performing well as compared with that of the existing FF-AOMDV.Â Â
Keywords: Energy Consumption; Power Aware; Load Aware; Routing Overhead; Energy Efficient Protocol; Fitness Function; FF-AOMDV; MANET; Multipath Routing; PLA-AOMDV.